Cytogenotoxicity assessment of 3-(3,4-dihydroxyphenyl)-7,8-dihydroxycoumarin on HepG2/C3A cells and leukocytes - Castanha, Ana Paula Martins (2022)
3-(3,4-Dihydroxyphenyl)-7,8-dihydroxycoumarin is a newly synthesized coumarin derivative with a potent antioxidant effect. The aim of the present study is to investigate the safety of this compound, determining the in vitro cytotoxic and genotoxic in human peripheral blood mononuclear cells (PBMC) and in HepG2/C3A cells. Cell viability has been investigated by the trypan blue staining test and MTT assay and the genotoxicity by the comet assay and micronucleus test, using concentrations between 0.01 and 10 μg/ml. The compound proved to be noncytotoxic in both cell lines, at all tested concentrations, protecting the cells from the DNA damage. In addition, this molecule does not show clastogenic/aneugenic effects when performing the micronucleus test with cytokinesis blockade. Based on the obtained data, and the conditions of the experiments, we can conclude that the 3-(3,4-dihydroxyphenyl)-7,8-dihydroxycoumarin is a safe molecule up to a concentration of 10 μg/ml, which encourages further studies aiming to explore its potential as a drug candidate.